2019 International Conference on Unmanned Aircraft Systems (ICUAS) 2019
DOI: 10.1109/icuas.2019.8798096
|View full text |Cite
|
Sign up to set email alerts
|

Below Horizon Aircraft Detection Using Deep Learning for Vision-Based Sense and Avoid

Abstract: Commercial operation of unmanned aerial vehicles (UAVs) would benefit from an onboard ability to sense and avoid (SAA) potential mid-air collision threats. In this paper we present a new approach for detection of aircraft below the horizon. We address some of the challenges faced by existing vision-based SAA methods such as detecting stationary aircraft (that have no relative motion to the background), rejecting moving ground vehicles, and simultaneous detection of multiple aircraft. We propose a multi-stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Some researchers [24] - [25] also reported that image classification-using bag of features and SVM as a classifier could significantly improve the accuracy of classification, as used in [26] to detect review spam on the labeled dataset of social media. Other recommend also categorizing the scenes like in Aircraft detection [27] - [28]. The texture characteristics and Gabor filtering method are used to reduce detection processing and computational complexity while refining detection effectiveness by 90%.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Some researchers [24] - [25] also reported that image classification-using bag of features and SVM as a classifier could significantly improve the accuracy of classification, as used in [26] to detect review spam on the labeled dataset of social media. Other recommend also categorizing the scenes like in Aircraft detection [27] - [28]. The texture characteristics and Gabor filtering method are used to reduce detection processing and computational complexity while refining detection effectiveness by 90%.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Based on our knowledge, similar detection only for locating airplanes, not the wreckages. Detecting multiple airplanes has been proposed by the work [13], a deep learning algorithm has been proposed detecting airplanes below the horizon with the feature able to reject moving vehicles. Images below the horizon also can have a highly cluttered background that makes detection nontrivial.…”
Section: Related Workmentioning
confidence: 99%
“…Deep Neural Networks (DNNs) have achieved high performance across many domains, such as speech processing [1], image classification [2], medical diagnostics [3], and social media [4]. DNNs have been deployed to support many mission-critical applications, including malware detection [5], aircraft detection systems [6] and autonomous vehicles [7]. There are increasing concerns about the generality of deep learning models, i.e., their limited performance on unseen samples beyond the training dataset.…”
Section: Introductionmentioning
confidence: 99%